Mitigation of oxygen presence in AlN (100) & (002) growth using RF magnetron sputtering - Bakri, Anis Suhaili (2022)
Aluminium nitride (AlN) nucleation layer (NL) is a useful nitride semiconductor for the growth of Gallium Nitride (GaN) on silicon. Major issues related to the fabrication of AlN films are on its crystallographic orientations and high processing temperatures. In order to fabricate AlN NL at low temperatures, radio frequency (RF) magnetron sputtering is used in this study. The aims are to deposit homogeneous and highly crystalline AlN NL with (100) and (002) preferential orientations at low processing temperatures. In this study, the homogeneous deposited AlN with highly crystalline along the (100) and (002) preferential orientations were successfully controlled using sputtering base pressure without any external heating. This will mitigate the presence of oxygen that presents during the deposition process. Moreover, the sputtering parameters such as target-to-substrate distance, working pressure, deposition times, and RF power were optimized. Thus, these highly crystalline AlN along the (100) and (002) preferential orientations were used in the Metal-Insulator-Semiconductor (MIS) structure to investigate their leakage currents. For the (002) preferential orientations of AlN, X-ray diffraction (XRD) showed that the full width at half maximum (FWHM) was smaller with low dislocation density and microstrain. Cross-sectional images from the field-emission scanning electron microscope (FESEM) showed that its exhibited grass-like columnar structures, showing it had a well-aligned structure. Meanwhile, its electrical properties showed that the (002)-oriented AlN NL had high electrical resistivity due to low dielectric permittivity, high capacitance, and low dielectric relaxation. The (100) and (002) preferential orientations leakage currents values in the MIS structure were 4.1 x 10-7 A and 2.0 x 10-8 A, respectively, indicating that (002) preferential orientations AlN NL displayed the lowest leakage current significantly. The effects of oxygen impurity in the layers played a crucial role in the growth of the (002) preferential orientations and acted as defects in the MIS structure, which increased the leakage current.